Damage Detection and Quantification Using Transmissibility Coherence Analysis - Yun-Lai Zhou; E. Figueiredo; N. Maia; R. Perera (Shock and Vibration)
A new transmissibility-based damage detection and quantification approach is proposed. Based on the operational modal analysis, the transmissibility is extracted from system responses and transmissibility coherence is defined and analyzed. Afterwards, a sensitive-damage indicator is defined in order to detect and identify the severity of damage and compared with an indicator developed by other authors. The proposed approach is validated on data from a physics-based numerical model as well as experimental data from a three-story aluminum frame structure. For both numerical simulation and experiment the results of the new indicator reveal a better performance than coherence measure proposed in Rizos et al., 2008, Rizos et al., 2002, Fassois and Sakellariou, 2007, especially when nonlinearity occurs, which might be further used in real engineering. The main contribution of this study is the construction of the relation between transmissibility coherence and frequency response function coherence and the construction of an effective indicator based on the transmissibility modal assurance criteria for damage (especially for minor nonlinearity) detection as well as quantification.